CuiZine the journal of Canadian food cultures = revue des cultures culinaires au Canada. (McGill University Library, 2008)
Cuizine: The Journal of Canadian Food Cultures / Revue des cultures culinaires au Canada nourishes intellectual exchanges on the subject of food in Canada from multicultural perspectives. Cuizine aims to provide an innovative academic forum for interdisciplinary discussions surrounding the diverse culinary cultures of Canada, while also providing a venue for dynamic creative content on the subject. Cuizine encourages submissions that emphasize site-specific regional foodways across the country, whether it is an historical examination of first generation Sri Lankan immigrant cooking in Toronto, a socio-economic study on the role of seal in Nunavut food culture, or a literary analysis of Duddy Kravitz's smoked meat escapades. At the same time, Canada's ethnic groups and cultural practices are not understood in isolation or as static phenomena. Rather, they evolve constantly and, in a nation of immigrants, interplay off each other. Cuizine hopes to foster this cross-cultural exchange by demonstrating the centrality of foodways to Canadian cultural identity. Cuizine also serves as a creative outlet for food-themed written and visual pieces. Poetry and prose submissions should feed our minds, and aesthetic pieces should engage our senses.